PERSPEKTIF ISLAM DALAM PENGELOLAAN SDA YANG EFEKTIF - Lili Ramahdani; Anisa Ramadhani (CV. Kalimasada Group, 2024)
Background Natural resources must remain available in order to sustain and support human life. Human need and dependence on natural resources is real, meaning that human life depends on the carrying capacity of natural resources. field research with a descriptive qualitative approach, data collection in this research is through observation, interviews, and documentation. Utilization of natural resources with an Islamic perspective, namely in utilizing natural resources, not over-exploiting which can cause damage. Basically, Al -The Qur'an has provided an ideal concept in managing natural resources. By returning humans to the noble values ​​contained in their respective religious scriptures, it is hoped that they will be more careful and responsible when they want to interact with the environment and manage natural resources.